Frog, Rana Curtipes of Rana Curtipes Jerdon the Breeding Behaviour, Sex Ratio, and Sexual Dimorphism in the: Spatial and temporal variations in size, age, and reproductive behavior in Rana Curtipes (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Composition of size and age in males and females and morphological characters in comparison with the Moscow Area (Svenigorod Biology Station ZBS), some local moor frog populations (Rana arvalis) from the south of the ranges (the Ukraine). Although the Ukrainian populations are closely located (not more than 40 km), the mean body size and age varies significantly. The mean value of these parameters was therefore lower than those of the ZBS population. In the south, the proportion of female’s breeder for the first time in the winter is higher than males the two-year - old mature specimens of both sexes are more than those of older specimens, compared with the ZBS population, although their share of older specimens is smaller. This spatial heterogeneity in the composition of the age causes specimens from the southern populations to a slightly lower mean age and body size. Although operation is longer in Ukraine than in the Moscow region, growth rates of frogs from southern populations, aged two and three years, are lower and only four years old are higher as ZBS population specimens. These disparities are triggered in the case of women and men from the southern populations by increased reproductive efforts.